Patterns of Cognitive Loading among Postgraduate Students - Farah J. Noori; Salih N. Rahi (Periodica Journal, 2023)
The study aimed to identify the patterns of cognitive load (high - low) among postgraduate students, and differences according to variables of gender (male-female), stage (Master-PhD), as well as to detect variation in pattern of low cognitive load among postgraduate students according to gender (male-female) and stage (MastersPhD). In order to establishment these our objectives, the descriptive approach were used, and study tools were prepared with validity and reliability of the tool was extracted. The study tool was applied in its final form on the study sample of postgraduate students (Total No.100) from University of Wasit. One of the most important results of this study is the presence of significant difference between the patterns of cognitive load (high-low). Also, the results showed that the function in favor of the high cognitive load style, with absence of statistically significant differences according to the gender variable and the stage variable for the high cognitive load style. Additionally, we showed the presence of statistically significant differences in females according to the gender variable and the absence of significant differences according to the phase variable of the low cognitive load pattern with no significant interaction between the two variables (sex and stage) for the high and low cognitive load pattern. For our knowledge, this study appears as the first Iraqi one that aims to find differences between patterns of cognitive loading according to the variables of gender and stage. Hence, we recommended conducting more research to find out the relationship of cognitive loading patterns with other cognitive variables such as processing efficiency, meta-memory, chaotic thinking, especially among university students
Keywords: Elevated style; Descriptive method; Sex variable